Post disaster adaptation management in airport: A coordination of runway and hangar resources for relief cargo transports. (October 2021) - Qin, Yichen; Ng, Kam K.H.; Hu, Hongtao; Chan, Felix T.S.; Xiao, Shichang
Highlights: Airport operations management under post-disaster relief scenario is studied. Runway and relief cargo resources management and coordination are considered. Integrated model is established to characterise the correlations between two bottleneck resources. Two-stage optimization method for airport management operations is proposed. Abstract: Air traffic congestions for processing relief cargos under post-disaster relief scenarios are common, due to high transport demands within a short time. To enhance the resilience of relief operations at airport, an optimization problem of relief air cargo transportations involving aircraft sequencing and loading/unloading within a designated hangar is studied in this paper. The objective is minimizing the tardiness in fulfilling inbound and outbound relief cargos. A mixed-integer linear programming model is formulated, which incorporates aircraft sequencing and hangar parking planning. To resolve the practical problem efficiently, we propose a two-stage optimization approach, which reduces complexity in solving the original model by coordinating the decisions of aircraft landing and take-off schedule and cargo hangar parking arrangement through iterations. The efficiency of the proposed method is examined through the computational results. High-quality solutions can be obtained by the two-stage optimization method within a reasonable time for practical implementation, which enhances the responsiveness and resource utilization of airport operations management under disaster relief situations.